Improvement of semifinished products technology: antioxidant properties of Ayurvedic syrups - Yakovenko, Petro; Omelchenko, Mariia; Kuzmin, Oleg (My University, 2024)
Дослідження присвячено удосконаленню технології напівфабрикатів шляхом посилення антиоксидантних властивостей аюрведичних сиропів з акцентом на рослинну сировину, органолептичні якості та розробку інноваційних кулінарних рішень

This study explores the improvement of semifinished product technology by enhancing antioxidant properties in Ayurvedic syrups, focusing on plant raw materials, organoleptic qualities, and the development of innovative culinary applications
Keywords: кафедра технології ресторанної і аюрведичної продукції; аюрведична кулінарія; сироп; полуниця; бадьян; ayurvedic nutrition; strawberry; star anise; syrup